Performance of humidity sensor based on photonic crystal fiber interferometer - Taher, Hanan J. (Iraqi Journal of Physics, 2019)
Photonic Crystal Fiber Interferometers (PCFIs) are greatly used for sensing applications. This work presents the fabrication and characterization of a relative humidity sensor based on Mach- Zehnder Interferometer (MZI), which operates in reflection mode. The humidity sensor operation based on the adsorption and desorption of water vapour at the silica-air interface within the PCF. The fabrication of this sensor is simple, it only includes splicing and cleaving the PCF with SMF.PCF (LMA-10) with a certain length spliced to SMF (Corning-28). The spectrum of PCFI exhibits good sensitivity to humidity variations. The PCFI response is observed for a range of humidity values from (27% RH to 85% RH), the position of the interference peaks is found to be shifted to longer wavelength with humidity increasing. In this work, a different length of PCFs are used, and the maximum humidity sensitivity of (5.86 pm / %RH) is achieved with (4.5cm) PCF length, and the rise time of (8sec) is achieved. This humidity sensor has distinguished features as that it does not require the use of a hygroscopic material, robust, compact size, immunity to electromagnetic interference, and it has potential applications for high humidity environments.